The Impact of Teacher Skills’ on Students’ Interest and Learning Outcomes - Firda, Syuknia; Khairat, Annisaul (International Journal of Education, Management, and Technology, 2023)
The influence of teacher competence on student interest and learning outcomes is a constructive way to help students correct mistakes and improve the quality of their learning. Teachers who have competence are able to identify all potential by providing a learning approach that suits students' needs. A teacher's competency can involve mastery of learning materials, ability to manage the class, ability to teach, ability to relate well. with students, as well as being able to communicate effectively with students. The purpose of this research was to determine the influence of teacher competency on student interest and learning outcomes. This research method uses a quantitative method, with the data collection method obtained by distributing online questionnaires whose validation has been tested. The results of this research explain that the influence of teacher competency can have a real, direct impact on influencing students, because teacher competency is very significant in influencing student interest and learning outcomes. And the results of this research can be concluded that a teacher's competence should not be improved, because efforts to improve the quality of learning must involve the competence that teachers have to provide understanding and skills in teaching to students. The researcher hopes that future researchers can carry out the same research but develop more thinking. critical by encouraging innovation in every step of the research. The researcher also recommends to future researchers to use this research as a reference in conducting research on the Influence of Teacher Competence on Student Interest and Learning Outcomes.